2021
DOI: 10.1186/s40317-021-00243-1
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic telemetry detection probability and location accuracy in a freshwater wetland embayment

Abstract: Background In recent years, large-scale acoustic telemetry observation networks have become established globally to gain a better understanding of the ecology, movements and population dynamics of fish stocks. When studying a species that uses different habitats throughout its life history difficulty may arise where acoustically suboptimal habitats are used, such as shallow, vegetated areas. To test the feasibility of active tracking in these acoustically suboptimal habitats, we quantified dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The significant effect of day-of-year is thus related to temperature rather than macrophyte growth or senescence. A single study, from a shallow (< 1 m) freshwater wetland, found a positive effect of macrophyte presence on detection probability, but this was explained as an artefact of the nested nature of the random effects that could not be accounted for in the study design [26]. The impact of Here positional accuracy and precision were significantly lower when transmitters were positioned within seagrass (0.9 m) compared to above (0.45 m) [27].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The significant effect of day-of-year is thus related to temperature rather than macrophyte growth or senescence. A single study, from a shallow (< 1 m) freshwater wetland, found a positive effect of macrophyte presence on detection probability, but this was explained as an artefact of the nested nature of the random effects that could not be accounted for in the study design [26]. The impact of Here positional accuracy and precision were significantly lower when transmitters were positioned within seagrass (0.9 m) compared to above (0.45 m) [27].…”
Section: Discussionmentioning
confidence: 98%
“…Performance of acoustic telemetry is poorly understood in shallow freshwater ecosystems with dense aquatic macrophytes [26,27,31]. Macrophytes are structurally complex and often considered as ecosystem engineers in freshwater ecosystems due to their key functions for ecosystem structure and functions [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When investigating the sequence of detections in space, range can be assessed specifically for migratory routes [50] or network analysis [38]. For fine-scale positioning, horizontal position errors would be quantified within an entire receiver array [8], potentially accounting for individual receiver's contributions [51] and system settings [52].…”
Section: Accounting For Rangementioning
confidence: 99%
“…Environmental impacts include static features, such as habitat type and bottom depth [2,3], as well as system dynamics that vary over time, such as wind, water currents, precipitation, biogenic and anthropogenic noise, temperature and stratification [4][5][6]. The detection range can also be dependent on the specifications of the equipment used, including transmitter type, transmitting power output and transmitter placement [7][8][9], as well as receiver depth, orientation and deployment method [5,10,11]. Biofouling on the receiver can significantly decrease receiver performance over time [12].…”
mentioning
confidence: 99%